A myiasis model for Philornis torquans (Diptera: Muscidae) and Pitangus sul-phuratus (Passeriformes: Tyrannidae) - López, Leonardo Rafael (2016)
The genus Philornis comprises neotropical parasitic flies that parasites bird nestlings in their larval stage. The ecology of most species of these parasitic flies is largely unknown. Here we present an epidemiological model that describes the behavior of parasite and host populations. The model was validated with real data of nestlings of the bird community present in a 30 ha area in Santa Fe, Argentina. It consists of two weakly coupled population models, one for the larval population and the other for the nestling population. It takes into account, among other things, the importance of age structure for both populations, the immune response rate on the host and larval survivor rate, the incidence of larval load on host death rate, along with others. This work presents a simple and intuitive way to represent the behavior of this complex biological system and it is a good starting point for future studies.